CONTINENTAL WEATHERING IN THE EARLY PRECAMBRIAN: SPECIFIC FEATURES OF MINERAL TRANSFORMATIONS AND COMPOSITION OF SUPERGENE SOLUTIONS - Alfimova N.A.; Matrenichev V.A. (My University, 2006)
The paper presents a detailed description of the geological structure, mineralogy, and chemical composition of the Archean weathering profile of granitoids in the Baltic Shield. Based on model calculations, the primary composition of granites in the substrate and weathering profile, as well as elemental composition of solutions draining the supergene profile, are determined. Model calculations for the Proterozoic weathering profile of analogous granitoids testify to the similarity of supergene alterations in the Early Precambrian. Mineral transformations during the weathering of granitoids are mainly expressed in the formation of minerals of new micas of the illite group against the background of large-scale decomposition of plagioclase. The composition of solutions in the hypergenesis zone of Precambrian weathering profiles sharply differs from the modern composition by lower contents of Ca2+ and K+ and the higher content of Fe2+. This is only possible under reducing conditions at high acidity of the diagenetic environment (pH < 6.5). The results obtained are essential for understanding the nature of unique Precambrian rocks (sedimentary iron ore rocks). The subordinate amount of carbonate sequences in Precambrian sedimentary sequences can be related to the specific composition of continental runoff primarily governed low-Ca supergene solutions. © Pleiades Publishing, Inc. 2006.
Keywords: Proterozoic; Archean; Precambrian::Proterozoic; Докембрий::Протерозой; Precambrian::Archean; Докембрий::Архей